2019
DOI: 10.1111/jcmm.14839
|View full text |Cite
|
Sign up to set email alerts
|

PNPLA3 I148M mediates the regulatory effect of NF‐kB on inflammation in PA‐treated HepG2 cells

Abstract: Both PNPLA3 I148M and hepatic inflammation are associated with nonalcoholic fatty liver disease (NAFLD) progression. This study aimed to elucidate whether PNPLA3 I148M is involved in NF-kB-related inflammation regulation in NAFLD. HepG2 cells homozygous for the PNPLA3 I148M mutation were used. The human PNPLA3 promoter sequence was screened for NF-kB binding sites using the MATCH and PATCH tools. NF-kB-mediated transcriptional regulation of the PNPLA3 gene was assessed by luciferase reporter assay, EMSA and Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…Furthermore, our results that doxepin treatment increased serum ALT and AST levels accords with the inability of FGF-21 to reduce the increased lipid accumulation in hepatocytes, resulting in lipid-overload stress and the subsequent release of multiple proinflammatory factors such as tumor necrosis factor (TNF) α and C-reactive protein (CRP) [ 51 , 53 ]—all leading to chronic low-grade liver inflammatory status. In addition, PNPLA3 may promote liver inflammation during NAFLD progression by increasing TNF-α expression and activating the endoplasmic reticulum stress-mediated and NF-κB–independent inflammatory inositol–requiring enzyme-1α/c-Jun amino-terminal kinase pathway [ 54 ]. In the last step of fatty acid biosynthesis, FASN exerts catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results that doxepin treatment increased serum ALT and AST levels accords with the inability of FGF-21 to reduce the increased lipid accumulation in hepatocytes, resulting in lipid-overload stress and the subsequent release of multiple proinflammatory factors such as tumor necrosis factor (TNF) α and C-reactive protein (CRP) [ 51 , 53 ]—all leading to chronic low-grade liver inflammatory status. In addition, PNPLA3 may promote liver inflammation during NAFLD progression by increasing TNF-α expression and activating the endoplasmic reticulum stress-mediated and NF-κB–independent inflammatory inositol–requiring enzyme-1α/c-Jun amino-terminal kinase pathway [ 54 ]. In the last step of fatty acid biosynthesis, FASN exerts catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is a well-known transcription factor that is involved in the inflammatory response ( 28 ). Western blotting analysis was performed to detect the phosphorylation of p65 and translocation of NF-κB p65 to the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…Research has revealed a significant correlation of FASN expression with the degree of steatosis in primary human hepatocytes in vitro as well as in experimental murine models and in the livers of patients with NAFLD in vivo [62]. Furthermore, hepatic inflammation may be promoted by PNPLA3 during NAFLD progression through an increase in TNF-α expression and activation of endoplasmic reticulum stress-mediated and NF-kB-related inflammation in NAFLD [63]. In addition, adiponectin has antidiabetic characteristics owing to its insulin-mimetic and insulin-sensitizing effects, and furthermore, anti-inflammatory and anti-atherosclerotic effects have been consistently reported [64].…”
Section: Discussionmentioning
confidence: 99%